Conventional nutritional indices and Composite Index of Anthropometric Failure: which seems more appropriate for assessing under-nutrition among children? A cross-sectional study among school children of the Bengalee Muslim Population of North Bengal,Indi (Italian Journal of Public Health, 2011)
Background: Stunting, wasting and under-weight have been conventionally utilized to assess the prevalence of under-nutrition among children. As these indices grossly underestimate this prevalence mainly due to overlapping of the children into multiple categories of anthropometric failure, there is a need for an appropriate single measure to assess this prevalence and identify the more susceptible individuals. The present study tries to ascertain whether the use of the Composite Index of Anthropometric Failure (CIAF) is more appropriate than the conventional indices for the estimation of under-nutrition among children.Methods: The present cross-sectional study was undertaken to compare the prevalence of under-nutrition using both the conventional indices and the CIAF among 1143 children aged between 5 years to 11 years (565 boys; 578 girls) belonging to the Bengalee Muslim Population (BMP), and residing in the district of Darjeeling, West Bengal, India. The children were selected using a multi-stage stratified random sampling procedure. The data was collected during the period from February 2009 to May 2010. Height and weight of the children were recorded using standard procedures. The conventional anthropometric indices and the CIAF were compared with the National Center for Health Statistics reference data to determine the prevalence of under-nutrition. A child having a value 2SD’s below that of the reference median in any of these indices was classified as suffering from under-nutrition. All the necessary approvals and consents were obtained from the Gram Panchayets and school authorities, and the study was conducted in accordance with the ethical guidelines for human experiments as laid down in the Helsinki Declaration of 2000.Results: Using the conventional indices, the prevalence of under-nutrition was observed to be 17.4% (wasting), 38.5% (stunting) and 47.0% (under-weight). However, with the use of the CIAF, this prevalence increased to 57.6% and included both single and multiple anthropometric failures. The prevalence of CIAF was observed to be higher among boys (60.4%) than girls (54.8%), although the differences were not statistically significant (chi-value = 0.96; d.f. 1, p> 0.05). Using the conventional indices too, boys were more affected than girls (stunting: chi-value = 0.20; d.f. 1, p> 0.05; wasting: chi-value = 1.94; d.f. 1, p> 0.05; under-weight: chi-value = 2.81; d.f. 1, p> 0.05).Conclusions: It is concluded that under-nutrition among BMP children is a serious health issue. According to our results, the majority of these childrenaged between 5 and 11 years were under-weight, followed by stunting and wasting. The use of the CIAF increased this prevalence. The potential advantage and appropriateness of using CIAF over conventional indices for evaluating child under-nutrition is discussed. Further studies are recommended for the comprehensive understanding of the scenario of under-nourishment in different Indian populations using CIAF. Nutritional intervention programmes are necessary to improve the nutritional status of the children covered in course of this study.
Keywords: under-nutrition; CIAF; children; Muslim; India